Effect of weed extracts against pulse beetle, Callosobruchus chinensis L. (Coleoptera: Bruchidae) of mung bean (Bangladesh Journal of Agricultural Research, 2016)
The n-hexane extracts of the weeds bhatpata Clerodendrum viscosum, kashiature Cassia tora, dhakishak Dryoptris filix-max, bonmorich Croton bonpalandianum and ghagra Xanthium strumarium were used to evaluate their effectiveness for suppressing pulse beetle, Callosobruchus chinensis reared on mung bean Vigna radiata grains. The investigations were done with 1, 2 and 4% n-hexane extracts of the weeds and an untreated control. The weed extracts exhibited considerable effectiveness which varied with weed species, concentrations and exposure durations. The higher concentrations showed the higher rate of insect mortality, fecundity, adult emergence inhibition, and grain protection. The LC50 values of the extracts ranged from 5.3 to 7.8, 4.7 to 6.5 and 4.1 to 6.0 g/100 ml at 24, 48 and 72 hours after treatment, respectively. The fecundity inhibition varied from 31.7 to 78.7%, adult emergence inhibition from 33.8 to 81.1%, and grain damage inhibition from 10.3 to 60.1% when bhatpata with concentration of 1 g/100 ml and ghagra with concentration of 4g/100 ml were applied, respectively. Among the tested weeds, ghagra (4g/100 ml) showed better efficacy against C. chinensis compared to other tested extracts and may be suggested to control pulse beetle and protection of mung bean grains.Bangladesh J. Agril. Res. 41(1): 75-84, March 2016